1984
DOI: 10.1111/j.0954-6820.1984.tb04979.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Iron Overload Using Transferrin Saturation

Abstract: People with parenchymal iron overload exhibit an elevated serum iron concentration and a raised transferrin (TIBC) saturation early in the course of the disease. They can therefore be detected by simple laboratory tests before organ damage has occurred. In this study running for 2 months, 10512 samples from approximately 8750 patients and blood donors were examined in a county hospital in Central Sweden. Abnormal TIBC saturation (>70%) was found in 1.7% of the samples. This abnormality was caused by physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…The screening limit for serum ferritin used in our study is rather high for women but even higher values are recommended for men (18). In a recent study serum fenitin of homozygotes of hemochromatosis, with a few exceptions, exceeded the level used in our study (9).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The screening limit for serum ferritin used in our study is rather high for women but even higher values are recommended for men (18). In a recent study serum fenitin of homozygotes of hemochromatosis, with a few exceptions, exceeded the level used in our study (9).…”
Section: Discussioncontrasting
confidence: 66%
“…The combination of these two methods is very efficient in identifying the hemochromatosis cases (18,19). However, as in other studies (9,11,20) these tests in combination also give a fairly large number of false positives, although the number of false negatives is extremely small. Most of the false positive men in our study consumed considerable amounts of alcohol (40-60 g/day) or showed some findings related to heavy alcohol consumption.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We observed the Same percentage of homozygous patients with hemochromatosis as in other northern European populations (33,36). This is most likely due to the variation in the frequency of the ancestral haplotype for hemochromatosis among the different study populations, and may be regarded as an indication of the northern European origin of this mutation (4,8,(43)(44)(45). Recent reports analyzing the distribution of the C282Y mutation in populations other than European support this hypothesis since the Tyr-282 substitution is very rare in the studied individuals (46,47).…”
Section: Discussionsupporting
confidence: 53%
“…We enrolled 10 adolescents and young adults with serum ferritin >300 ng/ml. Transferrin saturation >70% could be used as an additional criteria for iron overload [20]. The discrepancy of iron status determined by serum ferritin, transferrin saturation and hepatic MRI examination was shown in some patients.…”
Section: Discussionmentioning
confidence: 99%